2002
DOI: 10.3928/0022-0124-20020901-07
|View full text |Cite
|
Sign up to set email alerts
|

Changing Knowledge, Behavior, and Practice Related to Universal Precautions Among Hospital Nurses in China

Abstract: Purpose: To evaluate the effect of an educational training program for hospital nurses on universal precautions in Changsha, Hunan Province, People's Republic of China. Method: Using a quasi-experimental design, 50 of 100 randomly selected hospital nurses were randomly assigned to receive an educational intervention. Questionnaires were administered to the 100 nurses prior to and 4 months after the training. Findings: Knowledge, practice, and behaviors related to universal precautions and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
33
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 25 publications
6
33
0
2
Order By: Relevance
“…in Kerman, Iran, suggests that continuing education program promote knowledge, attitude and performance of nurses on documentation. [18] In a study conducted in Northern Italian University on effectiveness of a clinical skills workshop for drug-dosage calculation with participation of 77 nursing students, the results showed that clinical skills workshop increased drug-dosage calculation as well as students’ understanding of mathematical calculation,[19] which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 87%
“…in Kerman, Iran, suggests that continuing education program promote knowledge, attitude and performance of nurses on documentation. [18] In a study conducted in Northern Italian University on effectiveness of a clinical skills workshop for drug-dosage calculation with participation of 77 nursing students, the results showed that clinical skills workshop increased drug-dosage calculation as well as students’ understanding of mathematical calculation,[19] which is consistent with the present study.…”
Section: Discussionsupporting
confidence: 87%
“…[18] Huang et al . (2002) conducted a quasi-experimental study on evaluation of the effect of nursing educational programs among nurses in hospitals in China and reported an improvement in nurses’ knowledge, practice, and behavior after education,[19] which is consistent with this study.…”
Section: Discussionsupporting
confidence: 78%
“…For example, Huang focussed on increasing knowledge (educational training programme and written information) and awareness (clarifying risks for blood pathogen exposure), but also enhanced the self-efficacy of nurses with one hour of practical demonstration of hand washing and using gloves [55]. In Marra’s study, activities were also aimed at increasing awareness by providing feedback on infection rates.…”
Section: Resultsmentioning
confidence: 99%